IMPLEMENTATION OF SAK ETAP CHAPTER 11 CONCERNING CALCULATION OF MERCHANDISE INVENTORY AT MITRA MILK STORE - Dasaad Dasaad; Budi Wahyudi; Riyanti Riyanti; Dyah Palupi (International Journal Management and Economic, 2023)
This study aims to determine the application of the method of recording and valuing merchandise inventory based on SAK ETAP CHAPTER 11 which is appropriate for Mitra Susu Stores. The type of data used is quantitative data and the data source used is primary data. The data analysis technique with the inventory recording system used is the Perpetual system and the inventory valuation method used is the FIFO method and the Average method. The conclusion obtained is that Toko Mitra Susu has not implemented Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) CHAPTER 11, has not been recorded by any method which can cause errors in recording and calculating the valuation of merchandise inventory. The recording system that should be used is the perpetual system, because in this system the store does not have to carry out a physical inspection because it has been recorded in detail with an inventory card. The method that should be used is the FIFO method, because the COGS according to the FIFO method tends to be smaller than the Average method. Cost of Goods Sold will reduce income so that if the HPP is small it will increase profits, while a large HPP will reduce profits.